Faktor-Faktor Yang Mempengaruhi Kemauan Membayar Pajak Wajib Pajak Orang Pribadi (Studi Empiris Pada Kantor Pelayanan Pajak (KPP) Pratama Surakarta) - Sudharini, Winda Shinta (2016)
Taxes are a source of state revenue that is directly or indirectly received by the public in order to cover all the expenses of the country. The role of the taxpayer in the tax collection system is crucial to achieve the tax revenue. The number of taxpayers from year to year is improving, but there are still obstacles one level of taxpayer compliance with tax offenses vulnerable.Based upon the fact that we need to know the factors that influence the willingness to pay taxes individual taxpayers. The purpose of this study was to analyze the effect of the tax paying of conciousness, knowledge and understanding of tax laws, a good perception of the effectiveness of the tax system, the level of confidence in the system of government and law, the quality of service to the willingness to pay taxes. Population in this study are all individual taxpayers registered on KPP Pratama Surakarta. A sample is taken using Accidental Sampling, whereas the determination of the number of samples using the formula slovin. There are 78 questionnaire data.Primary data collection method used was survey by using questionnaire data. Data analysis method used in this research is multiple linear regression analysis using SPSS 16.0. The result showed that the variable pay tax awareness, knowledge and understanding of tax laws, a good perception of the effectiveness of the tax system, the level of confidence in the government and legal system, quality of service affect the willingness to pay taxes.